Implementasi Nilai-Nilai Pancasila Dengan Akulturasi Inovasi Teknologi Untuk Mencapai Effisiensi Pada Kegiatan Pemasaran dan Perdagangan Migas di Indonesia - Edy Soesanto; Divka Octavia Nurrochim; Sendy Dewanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The use of technology has become the main key in increasing efficiency in the oil and gas marketing and trading industry. This research investigates the implementation of Pancasila values ​​in the context of acculturation of technological innovation to increase efficiency in oil and gas marketing and trading activities in Indonesia. Through literature analysis, this research identifies Pancasila values ​​as a moral and ethical foundation that can guide positive transformation in business practices. This research also explores how technological innovations, such as digitalization and automation, can be combined with Pancasila values ​​to create a more efficient and sustainable system in the oil and gas industry. It is hoped that the results of this research will provide a better understanding of how technology influences efficiency in oil and gas marketing and trading, as well as provide useful recommendations for the oil and gas industry to utilize technology in accordance with the reference value of